Polish Football Teams in the Champions League - Does the Budget Decide Everything? - Tomasz KIJEWSKI; Jan A. WENDT (Editura Universităţii din Oradea, 2019)
The research on the participation of Polish football teams in the Champions League presented a retrospective view of the competition in one of the most important and prestigious football tournaments in Europe and the world. The article attempts to answer the question about assessing the budget size of individual football federations for the level of national leagues. The quality of national competitions largely determines the chances of a high place in the UEFA cup and additionally translates into the number of teams that take part in the competition. Taking the above into account, it can be assumed that the budget size of the national leagues football teams is positively correlated with their high achievements in UEFA competitions. Unfortunately, the Polish football league, compared to other European leagues, has relatively modest financial resources, which, according to the authors, is reflected in both the number of Polish teams participating in the group stage and their results.